Characterization of novel HLA‐A24:608N allele discovered in Koreans - Jeong, In Hwa; Lee, Jong Kwon; Kwon, Won Kyung; Song, Eun Young; Kim, Kyeong‐Hee; Lee, Jina; Jung, Sunmi; Jeong, Mijeong; Park, June‐Woo; Kang, Eun Suk (HLA, 2024)
A novel null HLA‐A*24 allele, HLA‐A*24:608N, was identified in five Korean subjects including three from a family and two separate individuals. This study was performed to discern its immunological function in transplantation settings. Because this null variant had deletions of approximately 12 k base pairs from intron 3 to 3′ end of the HLA‐A gene, low resolution HLA typing and amplicon‐based next generation sequencing (NGS) typing methods had failed to assign it. Hybrid capture‐based NGS method confirmed that this novel variant had a large deletion. T‐lymphocyte crossmatching by complement‐dependent lymphocytotoxicity and flow cytometry with a serum consisting anti‐HLA‐A24 antibody revealed negative results, implying that an individual with this allele would not carry a functioning A24 antigen. These findings highlight the importance of identifying a null HLA allele by employing appropriate molecular method and providing expected crossmatching outcomes in a real‐world transplantation setting.